What do cranial bones of LB1 tell us about Homo floresiensis?. Issue 93 (April 2016) - Balzeau, Antoine; Charlier, Philippe
Abstract: Cranial vault thickness (CVT) of Liang Bua 1, the specimen that is proposed to be the holotype of Homo floresiensis, has not yet been described in detail and compared with samples of fossil hominins, anatomically modern humans or microcephalic skulls. In addition, a complete description from a forensic and pathological point of view has not yet been carried out. It is important to evaluate scientifically if features related to CVT bring new information concerning the possible pathological status of LB1, and if it helps to recognize affinities with any hominin species and particularly if the specimen could belong to the species Homo sapiens. Medical examination of the skull based on a micro-CT examination clearly brings to light the presence of a sincipital T (a non-metrical variant of normal anatomy), a scar from an old frontal trauma without any evident functional consequence, and a severe bilateral hyperostosis frontalis interna that may have modified the anterior morphology of the endocranium of LB1. We also show that LB1 displays characteristics, related to the distribution of bone thickness and arrangements of cranial structures, that are plesiomorphic traits for hominins, at least for Homo erectus s.l. relative to Homo neanderthalensis and H. sapiens . All the microcephalic skulls analyzed here share the derived condition of anatomically modern H. sapiens . Cranial vault thickness does not help to clarify the definition of the species H. floresiensis but it also does not support an attribution of LB1 to H. sapiens . We conclude that there is no support for the attribution of LB1 to H. sapiens as there is no evidence of systemic pathology and because it does not have any of the apomorphic traits of our species. Résumé: L'épaisseur du crâne de Liang Bua 1, le spécimen proposé comme holotype de l'espèce Homo floresiensis, n'avait pas été décrite et analysée dans le détail, ni comparée avec des échantillons d'homininés fossiles, d'Hommes anatomiquement modernes et de microcéphales. Par ailleurs, la description paléopathologique du spécimen demeurait superficielle. Il était important d'évaluer si les caractères liés à l'épaisseur crânienne apportent de nouvelles informations sur l'état pathologique de LB1 et si cela aide à reconnaitre des affinités avec d'autres espèces d'homininés. L'étude avec un regard médical à partir de données microtomographiques permet d'établir plusieurs diagnostic rétrospectifs: sincipital T correspondant à une variation anatomique sans caractère pathologique; séquelle d'un traumatisme ancien frontal sans conséquence fonctionnelle évidente; hyperostose frontale interne sévère bilatérale qui a pu modifier la morphologie frontale antérieure de l'endocrâne de LB1. Nous montrons aussi que LB1 a des états pour les caractères étudiés, en relation avec la distribution de l'épaisseur osseuse, sa constitution interne et la configuration des structures crâniennes, qui sont plésiomorphes chez les homininés, du moins lorsque H. erectus s.l. est considéré relativement à H. neanderthalensis et H. sapiens . En complément, tous les crânes de microcéphales étudiés partagent les caractéristiques dérivées observées chez les Hommes modernes. Nous concluons qu'il n'y a aucun support à une attribution de LB1 à H. sapiens puisque son crâne ne ressemble à aucune pathologie connue et qu'il n'a aucun des caractères apomorphes de notre espèce. En revanche, les données d'épaisseur osseuse ne permettent pas de clarifier la définition de l'espèce H. floresiensis, ni de proposer d'hypothèses concernant l'espèce fossile dont ce petit Homme a hérité ses caractéristiques.